China's Accession to the World Trade Organization, Policy Reform, and Poverty Reduction : An Introduction - Bhattasali, Deepak; Shantong, Li; Martin, Will (Washington, DC: World Bank, 2014)
China's accession to the World Trade Organization (WTO) was a watershed event for both China and the WTO. After 30 years of effective isolation from the world economy, and close to a quarter century of autonomous reforms, China joined the legal framework of the world trading system. In doing so China made an extraordinarily wide-ranging set of commitments to reform of its own legal and administrative system and to thorough-going liberalization of trade in goods and services. This issue contains five studies from a major project undertaken by the World Bank and the Development Research Centre of China's State Council. A key objective of the studies was to assess the impact of the reforms associated with WTO accession on poverty in China, particularly in rural areas, which now lag so badly behind urban areas.